Community Knowledge and Interest in the Use of Removable Partial Dentures: A Study of Patients with Partial Tooth Loss - Riony Wijaya; Andrea Anderson Kie; Yabest Arron Sugiarto Saputra; Mega Merdekawati; Grace Monica; Dahlia Sutanto (International Journal of Health Engineering and Technology, 2026)
Partial tooth loss can lead to impaired chewing function, speech, and aesthetics, which negatively impact quality of life. One commonly recommended solution is the use of removable partial dentures (RPDs) due to their affordability and practicality. However, the use of RPDs remains low in the community, likely due to limited knowledge and low interest among the population. This study aims to determine the relationship between knowledge and interest in the use of RPDs among patients with partial tooth loss at BLUD UPTD Puskesmas Purwaharja 2, Banjar City. This is a descriptive observational study using a cross-sectional approach. The sample consisted of 96 respondents aged 45–59 years, selected through purposive sampling and meeting the inclusion criteria. Data were collected through a structured questionnaire assessing the level of knowledge and interest in RPDs. The results showed that most respondents had low knowledge (43.2%) but still demonstrated high interest (50.0%). Bivariate analysis using the Chi-Square test showed a significant relationship between knowledge and interest in the use of RPDs (p=0.000). These findings highlight the importance of dental health education as a strategic measure to improve acceptance and use of removable partial dentures in the community.